Expression of WW Domain-Containing Oxidoreductase WOX1 in Human Nervous System Tumors - Ming-Fu Chiang; Shur-Tzu Chen; Chen-Peng Lo; Chun-I Sze; Nan-Shan Chang; Yu-Jen Chen (Analytical Cellular Pathology)
Background and ObjectiveS: We aimed to evaluate the expression levels of the tumor suppressor WOX1 in nervous system tumors and its co-expression with p53 and neurofibromatosis type 2/merlin (NF2) tumor suppressor gene products.